2014
DOI: 10.1186/1471-2202-15-54
|View full text |Cite
|
Sign up to set email alerts
|

MAPT rs242562 and GSK3B rs334558 are associated with Parkinson’s Disease in central China

Abstract: BackgroundMicrotubule-associated protein tau (MAPT) is a neuronal protein involved in the pathogenesis of several neurodegenerative diseases including Parkinson’s Disease (PD). Glycogen synthase kinase 3 beta (GSK3B) catalyzes phosphorylation in multiple sites of tau protein. However, whether or not there is any association between the GSK3B gene alteration, MAPT haplotype and PD remains unexplored in Chinese population, especially in central Chinese population.ResultsHere, we aimed at studying the effect of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…However, the effects of ROCK and ROCK inhibitors on Bcl-2 in different types of cells have been controversial (Hippenstiel and others 2002; Ikeda and others 2003; Koch and others 2014), and no data have been published on the effect of ROCK inhibition on Bcl-2 in PD models or dopaminergic neurons. A number of previous studies have suggested the association between GSK-3β and PD (Duka and others 2007; Hernandez-Baltazar and others 2013; Yu and others 2014), and GSK-3β inhibitors have been suggested as potential therapeutic agents for the treatment of PD (Morales-Garcia and others 2013). Interestingly, it has been observed that ROCK inhibitors also inactivated GSK-3β in several types of cells (Hamano and others 2012).…”
Section: Mechanisms Involved In Rock-induced Dopaminergic Vulnerabilimentioning
confidence: 99%
“…However, the effects of ROCK and ROCK inhibitors on Bcl-2 in different types of cells have been controversial (Hippenstiel and others 2002; Ikeda and others 2003; Koch and others 2014), and no data have been published on the effect of ROCK inhibition on Bcl-2 in PD models or dopaminergic neurons. A number of previous studies have suggested the association between GSK-3β and PD (Duka and others 2007; Hernandez-Baltazar and others 2013; Yu and others 2014), and GSK-3β inhibitors have been suggested as potential therapeutic agents for the treatment of PD (Morales-Garcia and others 2013). Interestingly, it has been observed that ROCK inhibitors also inactivated GSK-3β in several types of cells (Hamano and others 2012).…”
Section: Mechanisms Involved In Rock-induced Dopaminergic Vulnerabilimentioning
confidence: 99%
“…As one of the isoforms of GSK-3, GSK3 β is widely expressed in tissues, especially in the brain [ 19 ]. GSK3 β , an important pathogenic protein kinase for PD, is activated by phosphorylation of Try216 residue located in the kinase domain and inactivated by protein kinase B- (Akt-) mediated phosphorylation of Ser9 residue [ 20 , 21 ]. GSK3 β is well-known for its role on glycogen metabolism, activation of transcription factors, and phosphorylation of tau proteins [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nine of these variants were linked to PD in at least two independent, unrelated cohort studies. They comprise: rs13312, a variant in the 3′-untranslated region of the ubiquitin-specific protease 24 gene ( USP24 ), associated with (PARK10) 85 , 86 , a susceptibility locus for PD; rs3766606, an intronic modification in the deglycase gene ( PARK7 ), linked with parkinsonism in Chinese and European populations 87 , 88 ; rs1801474 and rs1801582, two missense variants in the parkin RBR E3 ubiquitin-protein ligase gene (PRKN ), associated with PD risk 89 91 ; rs1800497, often correlated with neurological disorders, including PD, is located in the coding region of the ankyrin repeat and kinase domain containing the gene ( ANKK1 ), which controls dopamine synthesis in the brain 50 , 92 , 93 ; rs1801133, in the methylenetetrahydrofolate reductase gene ( MTHFR ), possibly implicated in PD 61 , 65 ; rs334558, a polymorphism in the glycogen synthase kinase 3 beta gene ( GSK3B ) potentially a protective factor for PD in Asian populations 94 , 95 ; rs6280, in the dopamine receptor D3 gene ( DRD3 ), implicated in both PD vulnerability and motor complications 96 , 97 ; and rs242562, a polymorphism in the microtubule-associated protein tau gene ( MAPT ), associated with PD 98 .…”
Section: Methodsmentioning
confidence: 99%